Layers of meaning or how to ‘connect the dots’: unveiling multimodal meaning-making in Greenpeace’s environmental videos. - Krysanova, Tetiana (Харківський національний університет ім. В.Н.Каразіна, 2024)
Meaning-making is perceived as an ongoing and dynamic process shaped by cognitive processes and influenced by social interactions. It results from the intersubjective interaction between meaning-makers and their audience, contributing to the construction of 'meaning-in-context'. My presentation aims to delve into the intricate layers of meaning embedded in Greenpeace’s environmental videos with the goal of enhancing public awareness of ecological issues and inspiring individuals to reconsider their perspectives on the environment. This necessitates the integration of two distinct approaches to the analysis of meaning-making in videos: cognitive-semiotic and multimodal. Ultimately, the emergence of meaning occurs on different layers, which overlap and integrate within the semiotic environment. This integration strategically combines logical reasoning and emotional impact, amplifying the persuasive efficacy and potential influence on viewers’ attitudes. The exploration of multimodal meaning-making in videos within this framework facilitates the identification of the semantic potential ingrained in varied semiotic elements and their skillful integration into a cohesive narrative.

Смислотворення є безперервним і динамічним процесом, що формується під впливом когнітивних та соціальних взаємодій. Це є результатом інтерсуб’єктивної взаємодії між творцями сенсу та їхньою аудиторією, сприяючи створенню «сенсу в контексті». Моя презентація спрямована на те, щоб заглибитись у складні шари значення, вкладені у екологічні відео Грінпіс, ​​щоб підвищити обізнаність громадськості щодо екологічних проблем і надихнути людей переглянути свої погляди на довкілля. Це зумовлює необхідність інтеграції двох різних підходів до аналізу смислотворення у відео: когнітивно-семіотичного та мультимодального. Зрештою, поява значення відбувається на різних шарах, які перекриваються та інтегруються в семіотичне середовище. Ця інтеграція стратегічно поєднує логічне міркування та емоційний вплив, посилюючи ефективність переконливості та потенційний вплив на ставлення глядачів. Дослідження мультимодального смислотворення у відео в рамках цієї системи полегшує ідентифікацію семантичного потенціалу, закладеного в різноманітних семіотичних елементах, і їхню вмілу інтеграцію в цілісну розповідь.
Keywords: когнітивна семіотика; cognitive semiotics; мультимодальність; multimodality; екологічне відео; ecological video; смислотворення; meaning-making; смисл; meaning; 81(082)